The State at Work, Volume 2 Comparative Public Service Systems - Edward Elgar (Cheltenham, UK • Northampton, MA, USA, 2008)
Internationally comparative projects take a long time to accomplish before results are finally published. For various reasons including multiple commitments of researchers, the initiative to projects like this often dates back ten years and more. In our case, work started with a fund provided for the period 1994–98 by the Humboldt Foundation in their Transco-op Program. This fund was co-founded by Pittsburgh University and the University of Bamberg, whom we thank for their support. Out of this initial two-country cooperation grew a preliminary comparative study of public services in the USA and Germany (Derlien and Peters 1998). This study set the framework for the second phase of the larger comparative project, for the country reports included in Volume 1 here. The initial funding enabled us to hold a conference in Bamberg in 1998, which brought together most of the teams represented in the two-volume work. The Bamberg conference was followed by similar conferences in Sandbjerg, Denmark (organized by Jørgen Grønnegaard Christensen and financed by the University of Aarhus Research Foundation) in 1999 and at the University of Strathclyde in Glasgow (organized by BrianW. Hogwood and financed by the Future Governance Program: Lessons from Comparative Public Policy) in 2000. Without these conferences during the take-off period of the project, much of the enthusiasm needed for a long shot like this endeavour would not have been generated. Our special debt, furthermore, goes to James Iain Gow, who not only contributed to these volumes, but also helped polish chapters written by authors whose native tongue is not the English language. The same job was done by Helen Nelson in several cases. To both of them we are deeply grateful. Also, we are indebted to those colleagues who were particularly engaged in this project, for their unrelenting emotional support and encouragement to complete this project. In a similar way, various people at Edward Elgar Publishing’s headquarters, who expressed continuing support for the project, are to be thanked. Finally, the tremendous job of bringing up the manuscripts to the publisher’s style requirements was done by Gisela Baumgärtner (Bamberg) with admirable precision, and Stefan Frank (Bamberg) assisted in cross-checking data and rearranging tabulations. We owe them thanks too.